النظرة العامة إلى تدريس اللغة العربية التعريف -األهمية -األهداف -المستويات (بحث في طرائق تدريس اللغة العربية) - Muhammad Sugianto (UNZAH Genggong, 2020)
Language plays a very important role in human civilization. With language, humanity preserves the treasures of its turath, both religious and cultural. Arabic, for example, has played this role for centuries. Even religious factors are the most dominant factor in learning Arabic among non-Arabs. In general, learning Arabic for non-Arabs can be interpreted as an activity that is intentionally carried out by someone to help other individuals in communicating using Arabic which is of course different from the native language used by these individuals in communicating before. Arabic is a foreign language which is very important to learn. At the very least, this urgency can be seen through the religious (read: Islamic) side of Arabic, which is the language of the Qur'an and Hadith as well as tura> th Islam. In addition, millions of Muslims in the world pray in that language. Arabic is also an official language that can be used in United Nations (UN) forums. Learning Arabic for non-Arabs aims so that these students can speak Arabic as native Arabs, have linguistic knowledge, and Arabic culture. In learning Arabic, students are usually classified into three levels: mubtadi`, mutawassit and mutaqaddim. Each of these levels has its own specifications that indicate their ability in the language and are not at all related to the level of formal academic studies being pursued. Keywords: Arabic learning, factors, urgency, level